Potential of Antimicrobial Peptides (AMPs) Extracted from Black Soldier Fly Larvae Against Vibrio parahaemolyticus In Vitro - Khanifa, Riskia; Ulya, Aida Himmatul; Darmawan, Ahmad Edi; Mahsunah, Anis H.; Mahardhika, Wahyu Aji (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Whiteleg shrimp (Litopenaeus vannamei) is one of the most widely farmed shrimp species; however, its cultivation is frequently threatened by vibriosis caused by Vibrio parahaemolyticus. To date, the potential of antimicrobial peptides (AMPs) derived from Black Soldier Fly (BSF) larvae as natural antimicrobial agents has not been reported. This study aimed to evaluate the effectiveness of BSF larval AMPs against V. parahaemolyticus, the causative agent of vibriosis in L. vannamei. Data were analyzed using a quantitative descriptive approach. The results showed that BSF larval AMPs contained protein levels ranging from 5.2–12.03% in the first trial and 9.19–10.82% in the second trial, while the water content varied between 4.77% and 77.89%. In vitro testing demonstrated that BSF larval AMPs inhibited V. parahaemolyticus growth with a 9 mm inhibition zone in all treatments. Further in vivo studies and optimization are necessary to develop BSF larval AMPs as sustainable, eco-friendly antimicrobial agents.